2017
DOI: 10.1097/ico.0000000000001256
|View full text |Cite
|
Sign up to set email alerts
|

Selective Localized Tenonplasty for Corneal Burns Based on the Findings of Ocular Surface Fluorescein Angiography

Abstract: We observed acceptable outcomes in our patients after selective tenonplasty based on ocular surface angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It can be a single early stage procedure, or combined with AMT. Anterior segment fluorescein angiography maybe considered to enable more selective localised tenonplasty [74]. It must be noted that Tenon advancement procedures are difficult in patients with acute injury due to the presence of friable and inflamed conjunctiva and Tenon's tissue.…”
Section: Sutureless Amniotic Membranementioning
confidence: 99%
“…It can be a single early stage procedure, or combined with AMT. Anterior segment fluorescein angiography maybe considered to enable more selective localised tenonplasty [74]. It must be noted that Tenon advancement procedures are difficult in patients with acute injury due to the presence of friable and inflamed conjunctiva and Tenon's tissue.…”
Section: Sutureless Amniotic Membranementioning
confidence: 99%
“… Selective tenonplasty is a procedure where limbal peritomy is performed in selected areas of limbal and scleral non-perfusion which are localized by FA. [ 28 ] Studies on this modification of tenonplasty have shown re-established perfusion, which was also confirmed on FA. [ 16 ] This procedure is less invasive when compared to a complete 360 degree limbal peritomy and may prevent the inadvertent removal of healthy limbal and conjunctival tissues.…”
Section: Surgical Techniquementioning
confidence: 75%
“…[ 16 ] This procedure is less invasive when compared to a complete 360 degree limbal peritomy and may prevent the inadvertent removal of healthy limbal and conjunctival tissues. [ 16 28 ] However, the procedure is dependent on FA or AS-OCTA confirmation of the ischemic area, and unavailability of these devices will limit the feasibility of the procedure. The combined use of an oral buccal mucous membrane with tenonplasty has been described in severe cases of scleral ischemia.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This procedure involves the advancement of Tenon's capsule to help re-perfuse the ischemic areas. The use of FA has been described to determine the area of limbal or scleral ischemia that will require the procedure, and the same purpose can be extrapolated to OCTA [49,50]. Furthermore, the extent of ischemia can be used to prognosticate the outcome in terms of vision and development of LSCD.…”
Section: Quantitative Assessment Of Limbal Vasculaturementioning
confidence: 99%